The Effectiveness of The Combination of Nanoparticles from Carica papaya L. Leaf and Chitosan 1% Against Fibroblasts in The Tooth Socket of Wistar Rats. - Mellisa Sim; Helen Theresia Nauli; Dang Phuong Khanh; Novelya; Felice Florencia Nicoline (Fakultas Kedokteran Universitas Sriwijaya, 2021)
Nanoparticles size can make easier for drugs to enter and react quickly to the body. In this study, nanoparticles Carica papaya L. leaf were used and combined with chitosan 1%. The aim of this study was to measure the effectiveness of the combination of nanoparticles from Carica papaya L. leaf and chitosan 1% against fibroblasts in the tooth socket of Wistar rats. Carica papaya L. leaf extract was made by maceration method and converted into a concentration of 25%, 50%, 75% and 100%, then made into nanoparticles using the nanoemulsion method. Chitosan 1% was made using Na-TPP solvent using the ionic gelation method with a ratio of 2:1 and after that it was mixed with nanoparticles of Carica papaya L. leaf then made into a gel preparation. The ANOVA statistical test shows a significant number of p <0.05, so it can be ignored that the increase in the number of fibroblast cells produced by the nano gel extract is 25%, 50%, 75% and 100%, its 138, 173, 177.4 and 328. Thus, the combination of 100% Carica papaya L. leaf nanoparticle extract and 1% nanocitosan was the most effective in increasing fibroblast cells on Wistar rat tooth socket.